47 patients with FLNA associated periventricular nodular heterotopia. Issue 1 (December 2015) - Lange, Max; Kasper, Burkhard; Bohring, Axel; Rutsch, Frank; Kluger, Gerhard; Hoffjan, Sabine; Spranger, Stephanie; Behnecke, Anne; Ferbert, Andreas; Hahn, Andreas; Oehl-Jaschkowitz, Barbara; Graul-Neumann, Luitgard; et al.
Abstract Background Heterozygous loss of function mutations within the Filamin A gene in Xq28 are the most frequent cause of bilateral neuronal periventricular nodular heterotopia (PVNH). Most affected females are reported to initially present with difficult to treat seizures at variable age of onset. Psychomotor development and cognition may be normal or mildly to moderately impaired. Distinct associated extracerebral findings have been observed and may help to establish the diagnosis including patent ductus arteriosus Botalli, progressive dystrophic cardiac valve disease and aortic dissection, chronic obstructive lung disease or chronic constipation. Genotype-phenotype correlations could not yet be established. Methods Sanger sequencing and MLPA was performed for a large cohort of 47 patients with Filamin A associated PVNH (age range 1 to 65 years). For 34 patients more detailed clinical information was available from a structured questionnaire and medical charts on family history, development, epileptologic findings, neurological examination, cognition and associated clinical findings. Available detailed cerebral MR imaging was assessed for 20 patients. Results Thirty-nine different FLNA mutations were observed, they are mainly truncating (37/39) and distributed throughout the entire coding region. No obvious correlation between the number and extend of PVNH and the severity of the individual clinical manifestation was observed. 10 of the mutation carriers so far are without seizures at a median age of 19.7 years. 22 of 24 patients with available educational data were able to attend regular school and obtain professional education according to age. Conclusions We report the clinical and mutation spectrum as well as MR imaging for a large cohort of 47 patients with Filamin A associated PVNH including two adult males. Our data are reassuring in regard to psychomotor and cognitive development, which is within normal range for the majority of patients. However, a concerning median diagnostic latency of 17 to 20 years was noted between seizure onset and the genetic diagnosis, intensely delaying appropriate medical surveillance for potentially life threatening cardiovascular complications as well as genetic risk assessment and counseling prior to family planning for this X-linked dominant inherited disorder with high perinatal lethality in hemizygous males.